Ethnic diversity and financial inclusion in post-apartheid South Africa - Isaac Koomson; Michael Danquah; Edward Martey (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
The ethnic diversity-financial inclusion nexus remains one of the least explored topics in the literature despite global attempts to promote cultural mixing due to its socioeconomic benefits. We contribute to the literature by examining the link between ethnic diversity and financial inclusion using five-wave panel data from South Africa, a country noted for its diverse ethnic groups with unique knowledge stock. We measure financial inclusion using a multidimensional construct, while ethnic diversity is conceptualized using fractionalization and polarization indexes. After addressing endogeneity using various quasi-experimental techniques, we find that ethnic diversity increases financial inclusion, with men and urban residents experiencing higher beneficial impacts of ethnic diversity. Further analysis reveals that increased employment opportunities and social group membership serve as potential pathways via which ethnic diversity increases financial inclusion. Carefully designed policies aimed at promoting ethnic diversity will go a long way to boosting financial inclusion.
Keywords: D03; D14; J15; 330; ethnic diversity; financial inclusion; employment; social groups; South Africa